THE INFLUENCE OF PERFORMANCE ALLOWANCE (REMUNERATION) ON THE PERFORMANCE OF EDUCATIONAL STAFF AT THE FACULTY OF FISHERIES AND MARINE SCIENCES, PATTIMURA UNIVERSITY - Leiwakabessy, Cliffy E; Ruhulessin, Lidia M (Manis: Jurnal Manajemen dan Bisnis, 2025)
This study aims to analyze the effect of performance allowances (remuneration) on the performance of educational staff at the Faculty of Fisheries and Marine Sciences, Pattimura University. The research employs a descriptive qualitative approach, with data collected through in-depth interviews and documentation. The findings indicate that the current performance allowance system has not fully provided an optimal incentive for improving the performance of educational staff. Several factors hinder its effectiveness, including a lack of understanding of performance evaluation indicators, limited communication of policies, and unequal distribution of allowances. This study recommends strengthening performance-based evaluation systems, enhancing transparency of information, and providing training to ensure educational staff better understand the performance allowance mechanism.